Karakteristik Penderita DM Dengan Ulkus Diabetikum Yang Dirawat Di Bagian Bedah RSUD Labuang Baji Makassar - Irwan, Irma Syanti; Wangi, Harakati; Rahmadani, Andi Anissa (Fakultas Kedokteran Universitas Bosowa, 2024)
Diabetic ulcers are a chronic complication of DM that can occur due to complications of macroangiopathy and microangiopathy, which cause vascular insufficiency and neuropathy. These risk factors are divided into risk factors that can be changed and risk factors that cannot be changed. The aim of the study was to determine the characteristics of DM patients with diabetic ulcers based on (1) age, (2) gender, (3) duration of DM, (4) HbA1c levels, (5) HDL levels, and (6) total cholesterol levels. This study included 55 diabetic patients with diabetic ulcers treated at the Surgical Department of Labuang Baji General Hospital Makassar from January 1, 2021 to December 31, 2022. This study used a retrospective descriptive method using secondary data in the form of medical records of DM patients with diabetic ulcers who were treated at the Department of Surgery at the Labuang Baji Hospital, Makassar. Data analysis was processed using SPSS software. The findings of this study show the distribution of DM patients with diabetic ulcers who were treated at the Surgical Department of Labuang Baji Hospital Makassar from January 1-2021 to December 31-2022, namely: (1) mostly in the elderly age group of 46-65 years (56.4%); (2) more women (54.5%) than men (45.5%); (3) more people with DM > 10 years (65.5%) than DM 10 years (34.5%); (4) more patients with HbA1c The conclusion of this study was that most DM sufferers with diabetic ulcers were in the elderly age group of 46–65 years, were women, had HbA1c levels >8%, HDL levels 45 mg/dl, and total cholesterol levels >200 mg/dl.